Low cost redesign of coil assemblies for ergonomic improvements / Loo Huck-Soo, Paul H.P. Yeow and Vimala Balakrishnan - Loo, Huck-Soo; Paul, H.P. Yeow; Vimala Balakrishnan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
This paper investigated into an alternative approach to solving cooling problems in two typical shopping complexes in Malaysia. For each case, an investigation was initially conducted to capture a general idea of poor indoor cooling suffered by the business operators and patrons. Ergonomics methods such as unstructured interviews and direct observations (DOs) were applied to obtain information on the major complaints. Visual inspections into the air handlers and the air ducts were also conducted. Subjective assessments (SAs) were utilized to test the response of the business operators. Cost accounting figures, both current and archival data pertaining to air handler maintenance service were retrieved and analysed. Ergonomic interventions were implemented by incorporating applied basic sciences into the rectification work. The original design specifications were modified to produce those for the new make. After new installations were in place, follow-up studies using similar methods (i.e. DOs, SAs, current and archival data) were conducted to assess the effectiveness of the interventions. It was found that the installations were cost effective. The new designs improved human comfort through effective heat removal from the air conditioned space. There were also cost savings in the maintenance of the new coil assemblies